limit sin(x-1)\x^2-1 as x->1
Use L'Hospital theorem
limit f(x)/g(x) = limit f'(x)/g'(x)
Here
limit sin(x-1)\(x^2-1) =
limit cos(x-1)/(2x) = 1/2
2007-02-01 02:08:49
·
answer #1
·
answered by catarthur 6
·
1⤊
0⤋
lim [ sin(x - 1) / (x^2 - 1) ]
x -> 1
That's what I'm assuming you mean (because that's the only way this question's answer is nontrivial.
To solve this, note that if we plug in x = 1, we will obtain the form
[0/0]. Therefore, one option is to use L'Hospital's rule. This involves taking the derivative of the top and bottom, and finding this new limit. Doing so, we get
lim [ cos(x - 1) / 2x ]
x -> 1
Plugging x = 1 into this limit, we get
cos(1 - 1) / 2(1) = cos(0) / 2 = 1/2
2007-02-01 02:10:04
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
A=sin(x-1)/(x^2-1)
(x^2-1)=(x-1)(x+1)
=>A=sin(x-1)/{(x-1)(x+1)}={sin(x-1)/(x-1)}{1/(x+1)}
put z=x-1=> x=z+1
=> => A={sinz/z}/(z+2)
i think that you are looking for the lim -->0
lim(sinz/z)=1
limA=1/(0+2)=>
=> limA=1/2
ok?
2007-02-01 02:09:19
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
x^2 -1 = (x+1)*(x-1)
When xâ1
Lt sin (x-1) / ( x^2 -1)
= Lt sin (x-1) / (x+1)*(x-1)
=Lt 1/ (x+1)* Lt sin (x-1) / (x-1)
=Lt 1/ (x+1) * 1 = ½.
2007-02-01 02:05:42
·
answer #4
·
answered by Pearlsawme 7
·
1⤊
0⤋
As x approaches what?
2007-02-01 01:55:14
·
answer #5
·
answered by Chris S 5
·
1⤊
0⤋
uh...
2007-02-01 01:59:15
·
answer #6
·
answered by Joe the God of Averageness® 4
·
0⤊
0⤋